2015
DOI: 10.1002/ajmg.a.37015
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine responsive megaloblastic anemia syndrome: A novel homozygous SLC19A2 gene mutation identified

Abstract: Thiamine responsive megaloblastic anemia syndrome (TRMAS) is a rare autosomal recessive disorder especially in countries where consanguinity is uncommon. Three main features are characteristic of the disease - megaloblastic anemia, early onset deafness, and non-type I diabetes. TRMAS is a Mendelian disorder; a gene SLC19A2 coding high affinity thiamine transporter mediating vitamin B1 uptake through cell membrane has been identified. We present the first patient with TRMAS in Lithuania - a 3-year-old boy born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…To date, more than 40 different SLC19A2 mutations have been identified in less than 60 families [18][19][20][21][22][23]. The majority of these have been described in individual case reports or small series and the focus has been mainly on the haematological manifestations of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 40 different SLC19A2 mutations have been identified in less than 60 families [18][19][20][21][22][23]. The majority of these have been described in individual case reports or small series and the focus has been mainly on the haematological manifestations of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the clinical condition of a 3-yearold male patient markedly improved several days after the initiation of daily supplementation with thiamine 100 mg. 13 In our case, anemia initially improved with 100 mg/day thiamine treatment. Hemoglobin level increased to 13 g/dl from 7 g/dl after 100 mg/day thiamine treatment.…”
Section: Discussionmentioning
confidence: 47%
“…TRMA is a rare syndrome, with less than 80 reported cases 8. To our knowledge, this case is the only one described in Switzerland.…”
Section: Discussionmentioning
confidence: 77%